Pipeline FFT Architectures Optimized for FPGAs. (9th August 2009) - Zhou, Bin; Peng, Yingning; Hwang, David
Abstract : This paper presents optimized implementations of two different pipeline FFT processors on Xilinx Spartan-3 and Virtex-4 FPGAs. Different optimization techniques and rounding schemes were explored. The implementation results achieved better performance with lower resource usage than prior art. The 16-bit 1024-point FFT with the R2 2 SDF architecture had a maximum clock frequency of 95.2 MHz and used 2802 slices on the Spartan-3, a throughput per area ratio of 0.034 Msamples/s/slice. The R4SDC architecture ran at 123.8 MHz and used 4409 slices on the Spartan-3, a throughput per area ratio of 0.028 Msamples/s/slice. On Virtex-4, the 16-bit 1024-point R2 2 SDF architecture ran at 235.6 MHz and used 2256 slice, giving a 0.104 Msamples/s/slice ratio; the 16-bit 1024-point R4SDC architecture ran at 219.2 MHz and used 3064 slices, giving a 0.072 Msamples/s/slice ratio. The R2 2 SDF was more efficient than the R4SDC in terms of throughput per area due to a simpler controller and an easier balanced rounding scheme. This paper also shows that balanced stage rounding is an appropriate rounding scheme for pipeline FFT processors.